Retención indebida del hijo y la necesidad de una reforma legal efectiva para la recuperación de niños, niñas o adolescentes en materia familiar - Roberta Carolina, Huacho Iturralde (2022)
ABSTRACT Children and adolescents are people who enjoy innate and inherent fundamental rights; it is an obligation of the state, society and the family to adopt political, administrative, economic, legislative, social and legal measures necessary for its effective compliance. The Constitution and the Childhood and Adolescence Code, mainly, have recognized a set of rights in order to guarantee the full and specialized protection of every human being, from their conception until they turn eighteen, however, in reality there are rights that are vulnerable from this priority care group. Allowing the integral development of the child is a difficult but not impossible task for the ones who have this responsibility, raising children in a healthy and successful way would be the ideal thing, but it does not always happen, since there are dysfunctional families, for which the custody of the children must be resolved, there are cases in which the person who has custody of the children tends to distance them from the parent who does not have custody, it is necessary that the visitation regime be respected, avoiding a possible undue retention, situation that occurs constantly in our country, it should be emphasized that there are many cases in every part of Ecuador in which it has not been possible to recover them immediately because of procedural delay, for this reason, the urgent need to propose a legal reform to COGEP that allows an expedited process has been carried out. Keywords: full protection, vulnerable groups, parent, improper retention, best interests of the child, legal reform. Firmado electrónicamente por: WASHINGTON GEOVANNY ARMAS PESANTEZ _____________________________ Reviewed by: Mgs. Geovanny Armas Pesántez ENGLISH PROFESSOR C.C. 0602773301